2014
DOI: 10.1136/bjsports-2014-093567
|View full text |Cite
|
Sign up to set email alerts
|

Practical experience with the implementation of an athlete's biological profile in athletics, cycling, football and swimming

Abstract: The introduction of the athlete's biological passport (ABP) has been a milestone in the fight against doping. The ABP is a collection of measurements of different biological parameters influenced by the administration of doping agents through the time and for each athlete. Two different modules have been developed and validated so far: the haematological module, which aims to identify enhancement of oxygen transport, including use of erythropoiesis-stimulating agents and any form of blood transfusion or manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…In order to detect illegal manipulation of blood and blood components, a mathematical model for detection of abnormal blood parameters, i.e., indirect evidence for blood manipulations, was introduced at the 2000 Olympic Games by Australian researchers and has since then been further refined by a group from the Swiss Laboratory for Doping Analyses with inclusion of more parameters and factors accounting for heterogeneity . Based on this initial work, the Athlete Biological Passport (ABP) was implemented in 2009 by WADA and the UCI and has proved its worth as the UCI has sanctioned more than 30 athletes based on abnormal blood profiles . An in‐depth review of the ABP is given elsewhere .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to detect illegal manipulation of blood and blood components, a mathematical model for detection of abnormal blood parameters, i.e., indirect evidence for blood manipulations, was introduced at the 2000 Olympic Games by Australian researchers and has since then been further refined by a group from the Swiss Laboratory for Doping Analyses with inclusion of more parameters and factors accounting for heterogeneity . Based on this initial work, the Athlete Biological Passport (ABP) was implemented in 2009 by WADA and the UCI and has proved its worth as the UCI has sanctioned more than 30 athletes based on abnormal blood profiles . An in‐depth review of the ABP is given elsewhere .…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Based on this initial work, the Athlete Biological Passport (ABP) was implemented in 2009 by WADA and the UCI and has proved its worth as the UCI has sanctioned more than 30 athletes based on abnormal blood profiles. [10] An in-depth review of the ABP is given elsewhere. [11][12][13][14] The ABP approach is based on the assumption that dopinginduced fluctuations in selected haematological markers can be determined at the individual level by continuous monitoring of these.…”
Section: Introductionmentioning
confidence: 99%
“…The development and implementation of the athlete biological passport into the antidoping practice has acted as a useful deterrent. 17 However, as outlined above, the proportion of adverse analytic findings from antidoping tests is well below the estimated prevalence of doping with sport. Antidoping authorities such as WADA and the AIU have therefore both suggested that there is a need for a more intelligence-led approach to antidoping in order to more effectively target test athletes.…”
Section: Discussionmentioning
confidence: 98%
“…The development and implementation of the athlete biological passport into the antidoping practice has acted as a useful deterrent . However, as outlined above, the proportion of adverse analytic findings from antidoping tests is well below the estimated prevalence of doping with sport.…”
Section: Discussionmentioning
confidence: 99%
“…It can provide information for subsequent target testing (e.g. regarding recombinant EPO or homologous blood transfusion) and independently indicate anti‐doping rule violations . However, longitudinal monitoring of blood parameters, modeling, and interpretation of measurement results necessitates a robust approach in which potentially confounding factors are accounted for.…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 99%